Mighty Stories, Dangerous Rituals : Weaving Together the Human and the Divine. - Anderson, Herbert (Jossey-Bass, 2001)
This moving and enlightening book presents us with a compelling vision of what can happen when we take the opportunity to connect stories and rituals - a vision of individuals and communities transformed through a deeper sense of connection to our loved ones, our communities, and God. Herbert Anderson and Edward Foley reveal how when stories and rituals work together, they have the potential to be both mighty and dangerous - mighty in their ability to lift us up and help us make these connections beyond ourselves and dangerous in challenging us to learn to live with complexity and contradictio.